Narratology and interpretation : the content of narrative form in ancient literature - Grethlein, Jonas, 1978-; Rengakos, Antonios (Trends in classics. Supplementary volumes ;, 2009)
The categories of classical narratology have been successfully applied to ancient texts in the last two decades, but in the meantime narratological theory has moved on. In accordance with these developments, Narratology and Interpretation draws out the subtler possibilities of narratological analysis for the interpretation of ancient texts. The contributions explore the heuristic fruitfulness of various narratological categories and show that, in combination with other approaches such as studies in deixis, performance studies and reader-response theory, narratology can help to elucidate the co.